Ways to optimize income tax and their impact on income budgets of the constituent entities of the Russian Federation - N. Z. Zotikov (Управление)
The relevance of the study is conditioned by the role and place of profit tax in the regional budgets revenues.   Unlike other taxes, the profit tax provides for many methods of tax optimization, the use of which will reduce the tax burden on a taxpayer and at the same time reduce regional budgets tax revenues. The state recognizes and accepts tax optimization if it is based on the current tax legislation provisions. Tax optimization means a taxpayer’s activity aimed at reducing tax payments and leading to an increase in the financial result, including the use of all tax benefits, tax exemptions, and other legal advantages provided by the current legislation. The application of some optimization methods depends on a taxpayer themselves, and some other ones depend on the regional authorities, for example, investment tax deduction.   The purpose of the study is to analyze the practice of profit tax optimization methods application and their impact on budget revenues and organizations income.   Common research methods have been applied such as analysis and synthesis, generalization, grouping, tabular method, etc. The article is based on the official data of the Federal State Statistics Service of the Russian Federation, the Ministry of Finance of the Russian Federation, and the Federal Tax Service of the Russian Federation, which ensures the reliability of the data used in the study.